REGIONAL DIFFERENCES OF THE URBANIZATION PROCESS - Yuldasheva Dilshoda Hoshimovna (Galaxy International Interdisciplinary Research Journal, 2023)
The urbanization process, their regional differences and types of modern urbanization process agglomeration, megalopolis are studied . The properties of the urbanization process in Uzbekistan are analyzed